Molecular cloning and characterization of SOCS2 from the mealworm beetle Tenebrio molitor. Issue 7 (23rd June 2019) - Kim, Bo Bae; Patnaik, Bharat Bhusan; Jo, Yong Hun; Bang, In Seok
Abstract: The suppressor of cytokine signaling (SOCS) family of proteins negatively regulate cytokine receptor signaling via the Janus kinase/signal transducer and activator of transcription (STAT) pathway. In this study, we discovered the SOCS2 homolog in the mealworm beetle Tenebrio molitor (TmSOCS2). The full‐length ORF sequence of TmSOCS2 was cloned, and expression pattern in the insect's developmental stages and tissues were investigated. TmSOCS2 encodes 254 amino acid polypeptide consisting of the conserved Src homology 2 (SH2) and SOCS box domains. The amino acid sequence of TmSOCS2 showed maximum 77% identity and minimum evolutionary distance of 0.228 with SOCS2 protein of another related beetle, Tribolium castaneum (TcSOCS2). In the phylogenetic tree, TmSOCS2 and TcSOCS2 formed a separate cluster showing evolutionary relatedness with the hemipteran bug Lygus hesperus SOCS2 (LhSOCS2). TmSOCS2 mRNA was maximally expressed in the egg stage of the insect. High relative expression of TmSOCS2 was observed in the Malpighian tubules during the insect's larval and adult stages. TmSOCS2 mRNA expression was significantly ( P  < 0.05) upregulated by E. coli challenge in the fat body tissue of T. molitor larvae. In hemocytes, early expression (at 3–6 h) of TmSOCS2 mRNA was observed after S. aureus and C. albicans challenge. Discovery and expression analysis of the SOCS2 homolog from the mealworm beetle T. molitor support transcript's putative involvement in the insect innate immune responses.